Menumbuhkan Generasi Qur'ani: Efektivitas Pembiasaan Sholat Dhuha pada MI Midanutta'lim II Jombang - Salsabila, Firdausi Maulidiyah; Munawir, Munawir (STAI Ihyaul Ulum Gresik, 2023)
This study aims to determine the effectiveness of habituation of dhuha prayer at MI Midanutta'lim II Jombang. This research uses a qualitative descriptive method with a type of case study research. The research location is at MI MI Midanutta'lim II Jombang. Data sources include primary and secondary data. This research uses descriptive qualitative methods. In collecting data, this research uses observation, interview, and documentation methods. The results of this study reveal that the habituation of dhuha prayers at MI Midanutta'lim II Jombang has been carried out effectively. Because dhuha prayers are included in the effective schedule of teaching and learning activities (KBM) at MI Midanutta'lim II Jombang. According to Mrs. Habibah and Mrs. Fauziyah as religion teachers, the habituation of dhuha prayers at MI Midanutta'lim II Jombang has been very effective and smooth. Although there is no attendance of dhuha prayers, the implementation of dhuha prayers at MI Midanutta'lim II Jombang runs smoothly. The obstacles and challenges in the implementation of dhuha prayer habituation in MI Midanutta'lim II Jombang are students who are late. Those who are late will be sanctioned with 6 salam or 12 rokaat dhuha prayers. However, it is very rare for students to be late. It can be concluded that the implementation of dhuha prayer habituation at MI Midanutta'lim II Jombang has been effective.